The Development of an Android-Based Educational Game “Orang Kayo Hitam” Jambi Folklore to Improve Student Motivation at Al-Falah Kindergarten Jambi (Universitas Negeri Semarang, 2022)
Fairy tales based on folklore are the right media to raise awareness of moral values. However, practically, it is often found that students are not interested in this kind of learning activity. The lack of interest in participating the learning activities can be caused by the learning media used by the teacher that is not attractive enough. This study developed and tested the feasibility and the effectiveness of an Android-based Orang Kayo Hitam Jambi folklore educational game. This study used the research and development method with the 4D model consisting of defining, designing, developing, and disseminating. The result of this study shows that the product feasibility assessment score through product validation from media experts was 3.8 (very feasible) and from material experts was 3.85 (very feasible). The effectiveness of this android-based Orang Kayo Hitam Jambi folklore educational game was tested through the hypothesis. The type of experimental research method used is One-Group Pretest-Postest Design in which the experiment is carried out in one group without a comparison group. The sample of this study were 30 students at Al-Falah Kindergarten. The result of the sig.(2-tailed) effectiveness test shows that the android-based Orang Kayo Hitam Jambi folklore educational game increases students' motivation in the learning process.